Geomorphological Characteristics and Their Implications for Development Planning in the Muaro Kalaban Area, West Sumatra, Indonesia - Gusti, Ugi Kurnia (Bulletin of Scientific Contribution, 2026)
Understanding geomorphic units and expressions is essential for development planning in areas undergoing tectonic deformation and active surface processes. Several factors such as variations in slope, landform type, and fluvial dynamics strongly influence the occurrence of possible geomorphic hazards such as landslides, erosion, and flooding. Muaro Kalaban area that is located in Sawahlunto City, West Sumatra, Indonesia, exhibits diverse geomorphic conditions that require detailed analysis to support sustainable development area planning. This study integrates field-based geomorphological observations with remote sensing analysis. Then followed with geomorphological mapping that was conducted through morphological and geomorphic process observation, focusing on erosion, weathering, geological structures, fluvial activity, and slope measurement and calculation. DEM derived parameters, including elevation and slope gradient, were used to delineate and validate geomorphic units and their spatial distribution. The results indicate that the study area consists of four main geomorphic units: denudational hills with moderate to steep slopes, denudational hills with gentle slopes, the Kepalakoto floodplain, and a meandering river channel. This study found that each geomorphic unit exhibits distinct surface processes and hazard potentials. The results revealed that denudational hills that are mostly associated with surface erosion and slope instability, while the floodplain and meandering river channel geomorphic units are characterized by fluvial processes and are prone to flooding and channel migration. This study inferred that geographical distribution and features of these geomorphic units emphasize significant limitations and challenges for development planning in Muaro Kalaban. By integrating geomorphological data into landuse planning perhaps can assist in identifying hazardprone areas, and also beneficial to promote sustainable development solutions which can reduce geomorphic risk..